Penerapan Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil dan menengah Tahun 2018 Pada Percetakan Undangan NSA Print Surabaya - Sharasshita Wirawan , Desak Gede Tiara; Khosyatillah, Nuroini (Fakultas Ekonomi, 2024)
The purpose of this study was to analyse the preparation of financial statements applied to NSA Print Surabaya as an entity engaged in the invitation printing industry. The type of research used is qualitative research with descriptive analysis method. The discussion is carried out by comparing the theory prepared by IAI regarding the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMK) with the implementation at NSA Print Surabaya and also providing recommendations for improving the preparation of financial statements based on SAK EMKM. Data obtained by evaluating documents related to the preparation of financial statements of NSA Print Surabaya as well as data obtained in the form of profiles, documents, and financial reports. The results showed that NSA Print Surabaya only recorded transactions by recording daily records in recording business financial transactions and did not yet have financial reports in accordance with accounting standards. In the application of the preparation of financial statements made by NSA Print Surabaya only has a simple recording of transactions that are booked, and balance sheet, profit and loss and CaLK reports that have not been made. So that recommendations provide financial report results that are in accordance with SAK EMKM. By preparing financial reports in accordance with SAK EMKM, the owner of NSA Print umkm will know the development of his business and make it easier for NSA Print to interact with external parties such as banks.